Sounds and letters. Book 6 - Hunt, Roderick (China, Oxford University Press, 2011)
Level 1+ Floppy's Phonics Sounds and Letters Books show all the sounds and graphemes from Phase 2 of Letters and Sounds in the context of Oxford Reading Tree scenes, packed with activities for practice and consolidation.